2012
DOI: 10.4028/www.scientific.net/amr.472-475.2726
|View full text |Cite
|
Sign up to set email alerts
|

CFD Study of Wake Interaction of Two Wind Turbines

Abstract: Understanding the wake behavior properly would help in designing proper layouts of wind farms to obtain maximum power and improved turbine life. This research aims at studying the impact of power of a turbine that is in the wake of another turbine under uniform inflow condition. Computational Fluid Dynamics (CFD) simulations are carried out to represent the velocity deficit behind two turbines in-line with the wind using the Virtual Blade Model (VBM). Power loss of the second wind turbine located at different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…As can be seen, a large body of research describes the wake characteristics of HAWTs and HATTs. Chick and Makridis [37] studied the wake interactions of two wind turbines at the top of an ideal Gaussian hill. They found that velocity deficits are higher in the flat terrain cases.…”
Section: Studies Using Vbmmentioning
confidence: 99%
“…As can be seen, a large body of research describes the wake characteristics of HAWTs and HATTs. Chick and Makridis [37] studied the wake interactions of two wind turbines at the top of an ideal Gaussian hill. They found that velocity deficits are higher in the flat terrain cases.…”
Section: Studies Using Vbmmentioning
confidence: 99%